BAHAYA TEKUK PONDASI TIANG LANGSING DALAM TANAH LUNAK KOHESIF - Indrastono Dwi Atmanto (Diponegoro University, 2011)
This paper treats the buckling of slender piles completely embedded in soft cohesive soils. Usually these soilswere assumed to behave elastically and were theoretically replaced by horizontal springs supporting the piles.However, soft soils deform as plastic materials. Therefore, it is suggested to assume a lateral supportindependent of the amount of the lateral displacement and accordingly to calculate a model; hereby the safetyagainst buckling of the piles is computed. It is shown that an ideally straight, centrally loaded pile does notbuckle until the stresses in the pile material exceed the elastic range. The shape of the pile axis, however, is mostimportant. Only a very little deviation from a straight line, because the pile is bent elastically or stressles, causesa rapid decrease of the maximum pile-load in dependency of the shear resistance of the soils with the increase ofthe deviation. The proposed model is also applied for eccentrically piles, i.e. a vertical load as well as a bendingmoment act on the pile top